Concreto reforzado con fibras de aluminio utilizando latas de reciclaje - Moran Gavilanes, Bryan (2024)
The main topic of this thesis is the use of recycled aluminum fibers, obtained from cans, as reinforcement in concrete. The objective of this study is to evaluate how the incorporation of these fibers affects the mechanical properties of concrete, including its compressive, tensile, and flexural strength, as well as its durability under various environmental conditions. The methodology employed includes conducting laboratory tests to characterize the materials and determine the optimal fiber proportions in the concrete mix. The sample includes different proportions of aluminum fibers, which were compared with traditional concrete and concrete reinforced with other types of fibers, such as steel and polypropylene. The results obtained showed that concrete reinforced with aluminum fibers presents significant improvements in compressive, tensile, and flexural strength compared to conventional concrete. Additionally, it was evidenced that aluminum fibers contribute to greater durability of the concrete, especially in corrosive environments. In conclusion, the incorporation of recycled aluminum fibers not only improves the mechanical properties of concrete but also represents a sustainable and economically viable alternative for the construction industry, promoting waste reduction and the use of recycled materials. This study lays the foundation for future research and practical applications of concrete reinforced with recycled materials.